Health-related quality of life among the elderly with heart failure: a generic measurement - Saccomann, Izabel Cristina Ribeiro da Silva; Cintra, Fernanda Aparecida; Gallani, Maria Cecilia Bueno Jayme (São Paulo Medical Journal, 2010)
CONTEXT AND ObjeCtive: Health-related quality-of-life (HRQoL) instruments have been greatly used among patients with heart failure (HF), although few of them are specific for elderly people. Among the generic instruments, the Medical Study 36-item Short-Form Health Survey (SF-36) is widely used. The aim here was to evaluate HRQoL among elderly individuals with HF through this generic instrument. DESIGN AND SETTING: Cross-sectional study at two university hospitals in São Paulo, Brazil. Methods: 170 elderly people with HF who were being followed up as outpatients were interviewed. To evaluate HRQoL, SF-36 was used. Results: The sample was composed of subjects with a mean age of 67.5 (± 6.2) years, with a diagnosis of HF for 65.9 (± 42.4) months, in functional class I (38.8%; 66) or II (42.9%; 73) and with reduced left ventricular ejection fraction (LVEF) (51.2%). The mental and social HRQoL domains did not seem to be compromised, since they presented high scores. Patients with HF typically had impaired physical capacity, which may explain the lower scores in the physical domain. Cronbach’s alpha coefficients were greater than 0.77 for all dimensions, except for general health status. Conclusion: The HRQoL measurements using SF-36 presented a high level of reliability when applied to Brazilian elderly individuals with HF. This population presented lower scores for the functional capacity and physical dimensions. This provides support for intervention studies aiming towards optimization of HRQoL in this group.